Test Antihyperglycemia Ethanol Leaf Extract Kembang Bulan ( Tithonia diversifolia) in Mice ( Mus musculus ) The Induced Diabetes With alloxan - Ronald Pasaribu; Salomo Hutahaean; Syafruddin Ilyas (Universitas Negeri Medan, 2015)
A research was conducted to invenstigate antihyperglycemic activity ethanol extract of leaf kembang bulan (Tithonia diversifolia) in mice with alloxan induced diabetes. The experiment used completely randomized design, 6 treatment groups with 5 replicates each. KP mice, P1, P2, P3 and P4 fasted for 16 hours and then injected intraperitoneally alloxan 5.04 mg. On day 4 post induction, KP, P1, P2, P3 and P4 positive diabetes. P1, P2 and P3 were treated 14; 42 and 70 mg/Kg of ethanol extract of kembang bulan while P4 were 0.9 mg/Kg glibenclamide for 12 days. The results showed that all treatment doses did not significantly affect body weight of diabetic mice (P>0.05). P1 obtained with a dose of 14 mg/Kg body weight is able to decrease blood glucose levels (P<0,05). The ethanol extract at a dose of 14 mg/Kg body weight effect on decreasing the number of giant cells of the spleen. It can be concluded ethanol extract of kembang bulan can lower blood glucose levels and effect the microstructure spleen of mice with alloxan induced diabetes. Keywords : Alloxan , Ethanol Extract , Tithonia diversifolia , Blood Glucose Levels.